Gdzie został ochrzczony Jezus i skąd to wiemy? - Murphy-O’Connor, Jérôme (The Biblical Annals, 2017)
According to the gospels, Jesus was baptized by John on the east bank of the Jordan, but apart from the fact that it was across the river from Jericho no details are given. The reports left by the earliest pilgrims and archaeological remains, permit us to pinpoint with a very high degree of accuracy the site venerated as the place of the baptism of Jesus in the Byzantine period. What interested pilgrims of all periods, however, was the water of the river in which by immersion they could renew their baptism. It was irrelevant to them whether they reached the water from the east bank or the west bank. Thus the current debate between Israel and Jordan is pointless.